CV-Type Onomatopoeia Phonological Structure in Shounen Manga - Mohammad Ali (Universitas Negeri Semarang, 2023)
Onomatopoeic vocabulary in Japanese is defined as a word that not only symbolizes the sounds/ sounds of living things such as animals and humans, sounds produced by inanimate objects, and sounds produced by natural phenomena. This study aims to describe phonological structures of CV-type onomatopoeia used in battle-themed shounen manga. This research's objects are all onomatopoeias used purely to symbolize sounds, movements, and conditions in the manga. This research was conducted using a descriptive method with a qualitative approach. The data sources for this study were eight titles of battle-themed manga series contained in the shuukan shounen manga tabloids published throughout 2018. The results of this study were the discovery of 41 types of phonological structures from CV-type onomatopoeia used in battle-themed shounen manga. Then, from the 41 types of phonological structures, it can be concluded that the tendency to use CV-type onomatopoeia in battle-themed shounen manga is onomatopoeia with phonological structures ending in a long sound (/R/). Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalOnomatopeiaJapanese PhonologyJapanese Pop Culture